Storage Is the New Black: A Review of Energy Storage System Applications to Resolve Intermittency in Renewable Energy Systems - Hans Joshua C. Conde; Christian M. Demition; Jaime Honra (Energies)
As the need for more sustainable methods of power generation becomes increasingly apparent due to the planet’s ever-deteriorating conditions, the quest for sustainable power generation intensifies. Among the options for sustainable power generation, the utilization of solar and wind power in large-scale applications is problematic due to the intermittent nature of their sources. Multiple solutions exist to counteract this intermittency, but energy storage systems are the most appealing. This article reviews the intermittency in renewable energy systems that rely on solar and wind, and how energy storage systems are utilized to mitigate this issue. While energy storage systems integrated into solar and wind power generation systems exhibit promising synergy and benefits, their full implementation is still hindered by a variety of challenges, which opens different fields of research to circumvent these challenges.